2014
DOI: 10.4081/ijas.2014.3148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Size on Performance and Egg Quality of Laying Hens During 20 to 36 Weeks of Age

Abstract: The aim of this study was to improve knowledge on the effect of group size on productive performance and egg quality of hens raised in furnished cages equally designed. A total of 520, 15-week-old Lohmann Brown laying hens were divided into 2 groups to have a similar initial body weight (average 1392±16.3 g). The cages of S25 group (240 L x 78 W x 50 H cm, 749 cm 2 /hen) hosted a total of 200 hens, while those of S40 group (462 L x 65 W x 50 H, 751 cm 2 /hen) included 320 birds. Experimental data were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
(24 reference statements)
1
13
0
2
Order By: Relevance
“…As known, in commercial strains the yolk weight increases with age [24,42] according to a higher food ingestion and lower request for body growth, but in our conditions in ER it did not change at 39 and 35 weeks of age, possibly due to an interaction between environmental conditions (high temperature), body growth, the laying activity and the hormonal status. Concerning the changes of eggshell incidence throughout the laying period according to the genotype, these may be due to interaction between environmental conditions and the physiological status of the birds: the hens laid eggs with different calcium depositions during each shell formation cycle or diluted the same calcium quantity over a larger surface [24,32] of the eggshell.…”
Section: Internal Traits Of the Eggsmentioning
confidence: 47%
“…As known, in commercial strains the yolk weight increases with age [24,42] according to a higher food ingestion and lower request for body growth, but in our conditions in ER it did not change at 39 and 35 weeks of age, possibly due to an interaction between environmental conditions (high temperature), body growth, the laying activity and the hormonal status. Concerning the changes of eggshell incidence throughout the laying period according to the genotype, these may be due to interaction between environmental conditions and the physiological status of the birds: the hens laid eggs with different calcium depositions during each shell formation cycle or diluted the same calcium quantity over a larger surface [24,32] of the eggshell.…”
Section: Internal Traits Of the Eggsmentioning
confidence: 47%
“…Variability in egg weight (10.8%) among different sources can affect different parts of eggs and quality of eggs as well as the consumer desire for eggs as consumer typically prefers larger eggs (USDA, 2000). Difference in eggs weight, on the other hand, could be attributed to age and stain of hens (Zita et al, 2009;Alsaffar et al, 2013), dietary protein/amino acids, energy and fat/fatty acids, housing density and housing condition (cages vs floor), health status, environmental stress and feed intake (Attia et al, 1994;Ahmadi and Rahimi, 2011;Goldberg et al, 2012;Bovera et al, 2014). It should be mentioned that hens in A, B, C and D groups were kept under similar common management and husbandry practice for laying hens under commercial table egg production.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Bovera et al. () concluded that internal quality of egg remains unaffected by group size in laying hens.…”
Section: Discussionmentioning
confidence: 96%
“…Waheda et al (1999) reported that albumen index and fresh albumen weight were higher in birds in the lower stocking density than those in other stocking density. On the contrary, Bovera et al (2014) concluded that internal quality of egg remains unaffected by group size in laying hens.…”
Section: Discussionmentioning
confidence: 98%